Homogeneity of Dynamically Defined Wild Knots - Hinojosa, Gabriela; Verjovsky, Alberto (Revista Matemática Complutense, 2006)
In this paper we prove that a wild knot K which is the limit set of a Kleinian group acting conformally on the unit 3-sphere, with its standard metric, is ho mogeneous: given two points p, q K there exists a homeomorphism f of the sphere such that f (K ) = K and f (p) = q . We also show that if the wild knot is a fibered knot then we can choose an f which preserves the fibers.